Situated identities and literacy pratices: to seem and to feel - Bartlett, Lesley (Scripta, 2013)
This article examines the centrality of cultural resources or artifacts in the social process of “doing literacy.” Relying on recent developments in sociocultural theories of continuous identity formation, I argue that people employ cultural artifacts to “seem” literate, or to be seen as literate by others, and to “feel” literate, that is, to develop a sense of themselves as literate. Drawing on ethnographic fieldwork in Brazil, I show how youth and adult literacy students use cultural artifacts in their efforts to perform literacy. In conclusion, I discuss the potential of sociocultural theories of identity formation for the field of literacy studies.